Durability Analysis of the Prototype Test Rig for Main Rotors - Scislowski, Karol; Skiba, Krzysztof; Wendeker, Miroslaw; Kliza, Rafal; Siadkowska, Ksenia; Lusiak, Tomasz; Novak, Andrej (Communications - Scientific Letters of the University of Zilina, 2022)
This paper presents an analysis of the strength of a prototype test rig for testing rotors of unmanned aerial vehicles. Digital design software was used for the design work that covered the creation of a virtual model of the test rig and strength analysis of its key elements. The paper discusses the test rig solutions, applied to date, of the small main rotor research. From the assumed operational parameters and structural parameters of the rotor, the main forces acting on the designed structure were determined: lifting force, reaction torque and empty mass of the test rig. Suitable actuators of the control system enabling the regulation of the total pitch and periodic pitch of the rotor, within the full range of the angle of attack, were selected for the rotor under test. The FEM (Finite Element Method) strength analysis was carried out for the proposed support structure and the correctness of the design was verified.
Keywords: FEA; digital design; rotors; CFD (Computational Fluid Dynamics); aircraft